2008
DOI: 10.1007/s00442-008-1072-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking summer foraging to winter survival in yellow pine chipmunks (Tamias amoenus)

Abstract: This study links summer foraging and scatter-hoarding to winter larder-hoarding and winter survival in yellow pine chipmunks (Tamias amoenus) by comparing patterns of time allocation and winter larder contents in 2 years with very different levels of resource availability. In 2003, seed production and the number of trees and shrubs producing seeds were high. In 2004 seed crops were small. Chipmunks allocated more time to foraging when food resources were scarce (66% in 2004) compared to when they were abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…However, they could have had access to some chemical cues expressed by flowers appearing in late April-May (Berger et al 1981). Second, chipmunks store enormous amounts of seeds in their burrows (Humphries et al 2002, Kuhn andWall 2008), which serves to decouple resource availability in their larder hoard from resource availability on the forest floor. For example, chipmunks had enough food in their burrows in a non-mast year to survive underground from July to May and presumably could have used these reserves to support current reproduction instead of survival for future reproductive opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…However, they could have had access to some chemical cues expressed by flowers appearing in late April-May (Berger et al 1981). Second, chipmunks store enormous amounts of seeds in their burrows (Humphries et al 2002, Kuhn andWall 2008), which serves to decouple resource availability in their larder hoard from resource availability on the forest floor. For example, chipmunks had enough food in their burrows in a non-mast year to survive underground from July to May and presumably could have used these reserves to support current reproduction instead of survival for future reproductive opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…obs.). Other studies have documented how summer foraging is strongly correlated with over-winter survival in fossorial squirrels (Kuhn and Vander Wall 2008). Likewise, marmots must obtain sufficient food to replace reserves, breed and then build up reserves again for the next winter.…”
Section: Activity Budget Of Marmots and Pastoralism Effectsmentioning
confidence: 99%
“…This is because increased energy intake during summer active months is strongly correlated with winter survival and reproduction (Kuhn and Vander Wall 2008). Recent studies of other marmot species have found a relationship between increased body mass gained over the active season and survival during hibernation, reproduction rates, and subsequent litter and population size (Ozgul et al 2010;Tafani et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…For example, density-dependent changes in time spent foraging may be caused by concurrent changes in the frequency of antagonistic interactions (interference competition Creswell 1997; Rutten et al 2010), per capita resource abundance (Kuhn and Vander Wall 2008), the degree of heterogeneity in the distribution of resources (Monaghan and Metcalfe 1985), or perhaps increased heterospecific attraction that leads to increased predation risk (Lima et al 1985;Hik 1995). These potentially confounding influences can be explored by experimentally manipulating the density of free-ranging animals using food supplementation (Boutin 1990) and/or predator exclusion (Karels and Boonstra 2000) or by adding (Svensson and Sinervo 2000;Calsbeek and Smith 2007;Rutten et al 2010) or removing (Sillett et al 2004;Meylan et al 2007) conspecifics to a study area.…”
Section: Introductionmentioning
confidence: 99%